Education for sustainable development and ICT: The case of MDP program at al-Farabi KazNU (Herald of Journalism, 2021)
Many universities from around the world – including in Kazakhstan – work on incorporating the Sustainable Development Goals (SDGs) into educational programs and the educational process as part of developing a new approach in adapting curricular and entire educational modules to realities of the modern economy, green development and global cooperation on Agenda 2030. The SDGs provide a new framework for organizing the learning process in higher education and moving it closer to both labour market needs and green economy demands. There are different views and approaches in dealing with new SDG-related educational agendas.The purpose of this article is to analyses the changing approaches to organizing the educational process and incorporating the SDG agenda into curricula, using the example of Kazakhstan. First, it as-sesses the theoretical aspects of incorporating an SDG agenda into the educational process by looking at how the Theory of Change has affected the formulation of the concept of education for sustainable development. Second, it analyses the international experience in developing programs on education for sustainable development by looking at the MDP program, a pioneering program developed by Columbia University in collaboration with the MDP global network. Third, it presents as a case study the introduc-tion of the MDP Global Classroom Program at Kazakh National University, Almaty, Kazakhstan, and discusses a decade of the program’s functioning in Kazakhstan (2011–20). The conclusion summarizes the findings of this article and discusses some implications for education policies and practices.Key words: Education for sustainable development, Information and Communication Technologies (ICT), Sustainable Development Goals (SDGs), Theory of Change, Kazakhstan, Central Asia.